Determinants of health-related quality of life in older primary care patients: results of the longitudinal observational AgeCoDe Study - Eisele, Marion; Weyerer, Siegfried (The British journal of general practice, 2015)
Background In older patients with chronic diseases, focusing on subjective, patient-relevant outcomes, such as health-related quality of life (HRQoL), is more pertinent than pursuing clinical or laboratory target values. Aim To investigate factors influencing the course of HRQoL in older (aged ≥78 years) primary care patients and to derive non-pharmacological recommendations for improving their quality of life. Design and setting A population-based prospective longitudinal observational study featuring data analysis from waves 2 to 5 of the AgeCoDe study, which was conducted in six cities in Germany. Method The HRQoL of 1968 patients over the course of 4.5 years was observed. Patients were, on average, aged 82.6 (±3.4) years and their HRQoL was measured using the EQ-5D visual analogue scale in a face-to-face assessment. Fixed-effects regression models were calculated to examine impact of change in potential influencing factors. This method allows unobserved heterogeneity to be controlled. Results The course of the participants’ HRQoL declined with increasing age, walking and incident hearing impairment. Increasing the number of physical activities improved the HRQoL. These findings were modified by sex, education level, and depression. Especially in females and patients with rather low education levels, increased physical activity improved the subjects’ HRQoL, while hearing impairment decreased it. Moving to an institution only improved the HRQoL in patients without depression or those with a low level of education (primary education). Conclusion Motivating patients to increase their weekly physical activity and to focus on preserving their ability to walk are promising approaches to improving HRQoL in older age. Less-educated patients and those without depression can also benefit from moving into an institution (for example, a care or retirement home).